Advances in hydroscience. - Chow, Ven Te, 1919-1981 (Academic Press, 1969)
Advances in Hydroscience, Volume 5 contains articles in three major areas of hydroscience, namely, stochastic hydrology, subsurface flow, and solid-state hydrology. This volume is composed of four chapters, and begins with a comprehensive review of the basic concepts, developments, and their potential application in stochastic hydrology, with emphasis on time series analysis and synthesis (model building). The next chapter deals with some of the advances in various scientific disciplines and their application to the analysis and prediction of seepage losses from open channels. These topics ar.